2017
DOI: 10.15403/jgld.2014.1121.263.jai
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric Laser Endomicroscopy for Barrett’s Esophagus – Looking at the Fine Print

Abstract: Barrett’s esophagus (BE) is a premalignant condition. The incidence of adenocarcinoma in BE has been reported to be between 0.1-3%. Dysplasia in BE is patchy and extensive biopsy sampling is labor intensive, low yield and does not eliminate the sampling error completely. Volumetric laser endomicroscopy (VLE) is expected to enable endoscopists to do targeted biopsy of dysplastic/cancerous lesions (not visible on white light endoscopy) among patients with BE. We reviewed 7 studies with a total of 62 subjects who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“… 16 That is why a lot of different endoscopy modalities and techniques were tried for visualization of dysplasia and precise biopsy, among them narrow‐band imaging (NBI), 50 , 51 , 52 acetic acid chromoendoscopy (AAC), 53 , 54 , 55 , 56 autofluorescence imaging (AFI), 57 , 58 confocal laser endomicroscopy (CLE) 59 , 60 , 61 , 62 , 63 and volumetric laser endomicroscopy (VLE). 64 , 65 , 66 Although some studies demonstrated different imaging modalities to be efficient, in other studies the use of these techniques did not report benefits in dysplasia detection rate. 67 , 68 , 69 , 70 Sensitivity of standard protocol with 4‐quadrant biopsy ranged from 28% to 85% in different studies and specificity varied from 56% to 100%, this led American Society for Gastrointestinal Endoscopy to set thresholds for any Preservation and Incorporation of Valuable endoscopic Innovations (PIVI) 71 : an imaging technology with targeted biopsies should have a per‐patient sensitivity of 90% or greater, negative predictive value (NPV) of 98% or greater for detecting HGD or early EAC and specificity of at least 80% to allow a reduction in the number of biopsies compared to standard protocol.…”
Section: Endoscopic Evaluation In Be and Eac: Standard Procedures And Computer‐aided Detection (Cad)mentioning
confidence: 99%
“… 16 That is why a lot of different endoscopy modalities and techniques were tried for visualization of dysplasia and precise biopsy, among them narrow‐band imaging (NBI), 50 , 51 , 52 acetic acid chromoendoscopy (AAC), 53 , 54 , 55 , 56 autofluorescence imaging (AFI), 57 , 58 confocal laser endomicroscopy (CLE) 59 , 60 , 61 , 62 , 63 and volumetric laser endomicroscopy (VLE). 64 , 65 , 66 Although some studies demonstrated different imaging modalities to be efficient, in other studies the use of these techniques did not report benefits in dysplasia detection rate. 67 , 68 , 69 , 70 Sensitivity of standard protocol with 4‐quadrant biopsy ranged from 28% to 85% in different studies and specificity varied from 56% to 100%, this led American Society for Gastrointestinal Endoscopy to set thresholds for any Preservation and Incorporation of Valuable endoscopic Innovations (PIVI) 71 : an imaging technology with targeted biopsies should have a per‐patient sensitivity of 90% or greater, negative predictive value (NPV) of 98% or greater for detecting HGD or early EAC and specificity of at least 80% to allow a reduction in the number of biopsies compared to standard protocol.…”
Section: Endoscopic Evaluation In Be and Eac: Standard Procedures And Computer‐aided Detection (Cad)mentioning
confidence: 99%
“…74 VLE is sensitive in identifying mucosal lesions that are invisible under standard WLE, thus allowing targeted biopsy of dysplastic/cancerous lesions. 75 The novel VLE laser marking system further enables direct in vivo marking of suspicious areas for targeted biopsy. 76 Imaging features of VLE found to be independently predictive of BE neoplasia included lack of layering, higher surface than subsurface signaling, and irregularly dilated glands/ ducts.…”
Section: Surveillancementioning
confidence: 99%